Propriedade: crise e reconstrução de um perfil conceitual - Lima, Getúlio Targino (2006)
The aim of the present work is to demonstrate that the property right has suffered a serious crisis in its conceptual profile conformation, which has to be rebuilt due to the symptomatic changes occurred in the contemporary law, referred to its subjective right nature, to the absence of property character in its focus and to the intersubjectivity of the juridical relation that it is constituted by, to the new possession role derived from it, all due to the application of the social function principle. The methodological procedure determined a general survey of the institute, in time and space, from the ancient times to the contemporaneity. Next, a view about the property conceptual crises, according to the Code texts, the matter of the juridical appearance and substance of the property and the conflict between the individual nature and the social function of the property. After that, the social function of the property, its conceptual idea, the social function of the possessions and the role of the property right, the view of the principle in the foreign law and, finally, the institute in the Brazilian civil Codes: the previous and the current ones. Pursuing the aim of the thesis, the following chapter deals with the construction of the new property right, to which were analyzed the following topics: the right to the property and the right of property, the property as an active and passive intersubjective relation, a matter of property statutes, to define or not the appearance of many properties and a final draw of a new profile of this right. Next, the possession was treated, mainly the one derived from the property, to define the real role to be performed in the new property, going from a mere projection or external image of control to essential instrument for the fulfillment of its social function and, consequently, legitimacy element of constituent title of this right. In the last chapter, the treatment of the property in the constitutional plan, specially focusing the study of the human being and the principle of preserving the dignity, which is concluded to be the main fundamental and justificative of the functional, intersubjective and supportive property, which travels from the mere individualism to its function